E-recruitment practices and adaptive performance / Syed Muhammad Izzuddin Syed Johari - Syed Johari, Syed Muhammad Izzuddin (Faculty of Business and Management, 2019)
The research for this project will be done on smaller scopes that involve Vouk Hotel Management. Vouk Hotel Management current has 19 hotels & resorts in 3 different country but this research is focusing on hotels & resorts in Malaysia. The research is done for employees that is in 16 hotel & resorts around Malaysia. In other words, focusing to conduct the research and investigate Vouk Hotel Management that implement e-recruitment. This research is important to know the influence of –recruitment practices on adaptive performance.